Evaluation of Universities’ Distance Education by Students and Academicians in the COVID-19 (Coronavirus) Period: A Qualitative Research - Samet Zengin; Fatih Kirkbir (Journal of Educational Issues, 2024)
The aim of the study is to evaluate the perspectives of students and academicians about distance education implemented by universities in the epidemic period and to determine the advantages and disadvantages of distance education to get an overall perspective. In the study, the data were obtained as a result of in-depth interviews with 12 students and 13 academicians. MAXQDA analysis program was used to analyze the data. The coded data were themed and analyzed. As a result of the analysis, concept maps were created and the analysis process was completed with interpretation. Conclusion of this study, the advantages and disadvantages of distance education applied by universities during the coronavirus period were evaluated. Recording the classes within the scope of distance education has given students the opportunity to review the classes. In this process, it is seen that education/training activities continue without any limitations on time and place. With distance education, it became possible to teach more than one class simultaneously. In this way, it became possible to reach more students in a shorter time. However, it has been found that the level of interaction between the academician and the student decreases in the distance education classes. As such, a decrease in motivation has been detected. Due to the COVID-19 pandemic, a rapid transition to distance education was made, and this rapid transition caused infrastructure and system problems. On the other hand, it is understood that a sound measurement and evaluation cannot be made in the exams applied in the distance education process.